2015
DOI: 10.1007/1345_2015_120
|View full text |Cite
|
Sign up to set email alerts
|

GFZ Global Multi-GNSS Network and Data Processing Results

Abstract: The Helmholtz Centre Potsdam GFZ German Research Centre for Geosciences (GFZ) is operating a worldwide Global Navigation Satellite Systems (GNSS) station network since many years. With recent developments in receiver technology and new upcoming navigation satellite systems like Galileo an upgrade of our stations was needed to track all GNSS. We will present the current status and setup of our station network and the plan for future upgrades. All modernized stations are presently contributing to the Multi-GNSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…Validation results shown by , but also analyses performed by, e.g., Prange et al (2016) and Uhlemann et al (2016), on their own MGEX products revealed that one of the most noticeable issues of the orbits of current Galileo IOV (In Orbit Validation) products are periodic orbit errors, whose amplitudes vary as a function of the elevation angle β of the Sun above the satellite orbital planes and that these orbit errors are mapped into the satellite clock corrections. demonstrated that the orbit errors with a once-per-orbit-revolution (1/rev) signature can be significantly reduced, if the ECOM1 is used together with an a priori box model.…”
Section: Introductionmentioning
confidence: 97%
“…Validation results shown by , but also analyses performed by, e.g., Prange et al (2016) and Uhlemann et al (2016), on their own MGEX products revealed that one of the most noticeable issues of the orbits of current Galileo IOV (In Orbit Validation) products are periodic orbit errors, whose amplitudes vary as a function of the elevation angle β of the Sun above the satellite orbital planes and that these orbit errors are mapped into the satellite clock corrections. demonstrated that the orbit errors with a once-per-orbit-revolution (1/rev) signature can be significantly reduced, if the ECOM1 is used together with an a priori box model.…”
Section: Introductionmentioning
confidence: 97%
“…The multi-GNSS solutions are a challenge for MGEX analysis centers due to the increasing number of satellites, new signals and observations types, and orbit modeling difficulties caused by different attitude steering modes as well as different satellites' sensitivities to perturbing forces. Currently seven MGEX Analysis Centers provide orbit and clock products of at least one new GNSS: (1) Center for Orbit Determination in Europe (CODE), Switzerland (Prange et al 2016), (2) Centre National d'Études Spatiales (CNES), France (Loyer et al 2012), (3) Deutsches GeoForschungsZentrum (GFZ), Germany (Uhlemann et al 2016), (4) Technische Universität München (TUM), Germany (Steigenberger et al 2013), (5) Wuhan University (WU), China (Guo et al 2015), (6) Japan Aero-space Exploration Agency (JAXA), Japan (Kasho 2014), and (7) European Space Agency (ESA), Europe (Springer et al 2012). Comparisons of orbit and clocks provided by different MGEX Analysis Centers can be found in Steigenberger et al (2015); Guo et al (2017), and Prange et al (2017).…”
Section: Igs Mgex Campaignmentioning
confidence: 99%
“…During the past three decades, the global or regional GNSS (Global Navigation Satellite System) station networks have been constructed for various applications [1][2][3], and nearly thirty years' of position time series of a larger number of permanent stations have been derived using GNSS tracking data. Thanks to these position time-series data, various geophysical phenomena, such as plate tectonics [4], crustal deformation [5], post-glacial rebound [6] and vertical land motion at tide gauges [7], have been investigated more clearly.…”
Section: Introductionmentioning
confidence: 99%